High perfomance athletics in Portugal: study of the quality in sport agents - Matos, Abreu; Correia, Abel (Journal of Physical Education (Maringá), 2008)
The present study, by evaluating the satisfaction of the high performance Athletics practitioners, aims to determine the quality of the service offered to them. The high performance main operational goal — the results and the excellence rankings — is related to a qualified strategic management service. Accordingly, the study was performed to know the level of satisfaction of those to whom the sub-system is oriented, contributing, thus, to the improvement of both the polices to be developed, and the service organized. The conclusions allowed by the high performance athletes and their personal coaches statements, during the Olympic cycle in Sydney, pointed out to a medium level of global satisfaction. According to the findings of this investigation, the inquired people consider that the federation: 1 – has accomplished the emerging requirements for the high performance, and that its responsible team has a reasonable leadership capacity; 2 – has discerningly applied the available resources, considering that the existent constraints do not lead to a causal relation with the technical goals; 3 – has provided efforts in a medium effective way concerning the modernization of the functioning processes of the high performance service; 4 – has a low efficient inter-personal relationship with athletes and coaches.